The Influence of Financial Literacy, Self-Efficacy, and Coping Strategies on Students' Finances - Syahwildan, Muhamad; Hidayah, Zulfa Zakiatul (Yayasan Ilomata, 2024)
Students with financial behavior that tends to be consumptive have a negative impact on financial behavior, new experiences as students and employees with limited income and various expenses must be able to be managed properly to be able to produce good financial behavior. This study aims to determine the effect of financial literacy on financial management behavior and to analyze the psychological effect of Self-Efficacy and Self-Coping on financial management behavior of undergraduate students in the management study program at Pelita Bangsa University. The research method used is quantitative with data sources taken by distributing questionnaires. Sampling used is by simple random sampling method. The population in this study were all students of the management study program in 2022 with a total of 4995, with a sample of 98 respondents obtained from the Slovin formula. The results of the research tested with SmartPLS 3.0 show that financial literacy, self-efficacy, and self-coping have a significant effect on financial behavior.